PENERAPAN PENDEKATAN CTL (CONTEXTUAL TEACHING AND LEARNING) UNTUK MENINGKATKAN PEMAHAMAN KONSEP MATEMATIS SISWA SEKOLAH DASAR - Tari Nurmala Pratiwi, - (2019)
This research aims to improve understanding of mathematical concepts in fifth grade students of Elementary School. The subject of this research were nineteen people, including six female students and threeten male students. This class action research model uses the Kurt Lewin model. Data collection techniques carried out in this study were written tests and participatory observations. This written test aims to measure the understanding of students mathematical concepts with the form of questions that are adapted to indicators of understanding mathematical concepts. While participatory observation is carried out by two colleagues by filling in the observation sheet during the learning process. With the data collection technique, researchers can write a description related to the development of understanding the mathematical consepts of students in each cycle. The indicators of understanding concepts used in this research are four, including restating an object, applying an object to problem solving, selecting particular procedur, and representing an object in a mathematical sentence. The results of an increase in understanding of the mathematical concepts of five A class students at SDN X are quite significant. More than a few students in the class have experienced an increase in indicators of understanding mathematical concepts in each cycle. This suggests that the CTL (Contextual Teaching and Learning)'s approach can improve the understanding of mathematical concepts of students in the five A class at SDN X, Cidadap Subdistrict, Bandung City.